SWOT Analysis of the Mempawah Regency Baznas Development Strategy in Collecting Zakat Funds - Eko Bahtiar (Journal of Islamic Law)
This study departs from the analysis of the development strategy of Mempawah District Baznas in collecting zakat funds. The main problem of this paper is to at least talk about the strategies carried out by Baznas officials so that people in Mempawah want to pay their zakat because in their community they issue less zakat to Baznas, the community issues more zakat for religious leaders. Then from the strategy analyzed using SWOT, a descriptive qualitative study began to describe the symptoms in the field. The research found that Baznas Mempawah District has the power to have zakat collection units for each office that has distributed their zakat to Baznas, many government employees have issued their zakat to Baznas. The threat of Baznas District Mempawah, namely: People are divided into paying zakat, Baznas promotion is still less intensive. The Baznas opportunity is the only BAZ in Mempawah Regency. There is a letter from the District Head of Mempawah regarding the regulation that employees must issue their zakat at Baznas. The threat is that Amil has formed many zakat institutions in each office. Strategies adopted by Baznas District of Mempawah When power meets opportunity, one must build a partnership between BAZ and LAZ so that it is easy to collect funds from the community. Baznas Strategy When Weakness meets opportunity, it increases the quality and quantity of competent resources for young people. Baznas strategy when power meets threats namely; entered into a collaboration between BAZ and UPZ so that UPZ could assist BAZ in collecting zakat from the community. Baznas strategy when weakness meets threats; that is, conducting training for young people, so that young people will be interested in joining Baznas.